Using Citizen Science to Incorporate Research into Introductory Biology Courses at Multiple Universities. (1st December 2021) - Vance-Chalcraft, Heather D.; Gates, Terry A.; Hogan, Kelly A.; Evans, Mara; Bunnell, Anne; Hurlbert, Allen H.
Although participation in citizen science has been hypothesized to have many educational benefits for undergraduates, little work has been published on this topic. We asked whether biology content knowledge and increased undergraduate engagement could be attained through involvement in citizen science. Across three universities, we included Caterpillars Count! as a research experience in introductory biology courses. This citizen science project measures seasonal variation in the abundance of arthropods on the foliage of trees and shrubs. Undergraduate students learned to survey plants for arthropods, add their observations to a large dataset, and use this national dataset to address questions. Each institution chose to emphasize slightly different content from the project and spent different amounts of time on it in class. Over five semesters, more than 1, 200 students participated in a pre- and post-assessment of knowledge related to citizen science, ecology, and the nature and process of science. A subset of students also provided written reflections. Students at all three institutions showed significant knowledge gains. The topics showing the largest gains across institutions were most related to the citizen science project, including concepts related to arthropod identification and a proper understanding of what citizen science is. These results support the use of citizen science in introductory courses to engage students, to improve learning, and to increase students' spirit of discovery.